Passport to nowhere [electronic passport with biometric information]. - Ross, P.E (IEEE spectrum)
Undue haste led the US government and the 27 countries in its visa-waiver pool to start a program to embed radio-tagged ICs in passports. These chips encode the physical characteristics of the bearer starting with the face. Its goal is to provide foolproof passport identification using a combination of biometrics and secure radio tagged ICs. The US initiative, included in the Enhanced Border Security and Visa Entry Reform Act of 2002, gained overwhelming support in the US congress and among the other 27 countries. Because of foot dragging and incompatible technologies, the system could not make its planned rollout and had to be postponed for a year. It was found that electronic passports wouldn't stop terrorists from getting into the country, which means that the reason for its development was not achieved. This paper discusses the factors, which made electronic passports not a suitable solution.